2014
DOI: 10.1080/09168451.2014.921558
|View full text |Cite
|
Sign up to set email alerts
|

(2-Nitroethyl)benzene: a major flower scent from the Japanese loquat Eriobotrya japonica [Rosales: Rosaceae]

Abstract: (2-Nitroethyl)benzene was identified as a major component of the flower scent of the Japanese loquat Eriobotrya japonica [Rosales: Rosaceae], together with p-methoxybenzaldehyde and methyl p-methoxybenzoate. The corresponding volatiles from chopped leaves did not contain these three compounds. This is the first time that 1-nitro-2-phenyl-ethane has been demonstrated to be a natural product among Japanese plants, although two Japanese millipedes are known to possess the same aromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
2
13
1
Order By: Relevance
“…In the recent biosynthetic study of the flower volatiles from the Japanese loquat Eriobotrya japonica, however, the presence of 13 has been lost [12] together with seven benzenoids (1, 5, 7, 8, 11, 15 and 16), with unknown reason. On the other hand, zingerone and phenethyl benzoate have not been detected in our results [1].…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…In the recent biosynthetic study of the flower volatiles from the Japanese loquat Eriobotrya japonica, however, the presence of 13 has been lost [12] together with seven benzenoids (1, 5, 7, 8, 11, 15 and 16), with unknown reason. On the other hand, zingerone and phenethyl benzoate have not been detected in our results [1].…”
contrasting
confidence: 78%
“…The adsorbed flower volatiles, after eluted with hexane, were analyzed by a gas chromatography coupled with a mass spectrometry (GC/ MS) analysis. The following 15 aromatic compounds (benzenoids) have been recovered; styrene (1), benzaldehyde (2), 2-phenylacetaldehyde (4), methyl benzoate (5), 2-phenylethanol (6), 2-phenylacetonitrile (7), 1,4dimethoxybenzene (8), (Z)-2-phenylacetaldoxime (9), 4-methoxybenzaldehyde (10), (E)-2-phenylacetaldoxime (11), 4-methoxybenzyl alcohol (12), (2-nitroethyl)benzene (13), methyl 4-methoxybenzoate (14), methyl cinnamate (15) and ethyl 4-methoxybenzoate (16), along with five terpenoids, as reported [1]. Among them, (2nitroethyl)benzene (13,32.7%), 4-methoxybenzaldehyde (10,27.3%) and methyl 4-methoxybenzoate (14, 24.6%) has been the major components.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that loquat flowers produce volatile benzenoids, including phenylacetaldehyde, phenethyl alcohol, and 2-phenethyl benzoate (Koeduka et al 2016b), whereas loquat leaf volatiles are mostly composed of C6 compounds such as (Z)-3-hexenyl acetate and (Z)-3-hexenyl butanoate (Kuwahara et al 2014). The levels of the EjAADC1 transcript were higher in loquat flowers than in leaves and increased throughout flower development.…”
mentioning
confidence: 98%
“…We previously reported that phenylacetaldehyde, phenylethyl alcohol, and 2-phenethyl benzoate are characteristic scent components of loquat (Eriobotrya japonica) flowers (Koeduka et al 2016a(Koeduka et al , 2016bKuwahara et al 2014). However, the gene responsible for biosynthesis of volatile phenylacetaldehyde in loquat has not been identified to date.…”
mentioning
confidence: 99%